Food and Nutritional Assessment in Schoolchildren from Mountainous Areas of Argentinean Northwest - de Piero Belmonte, Alexia Juliana (2017)
Background: Previous studies in Argentinean northwest found nutritional problems that could affect especially children, in process of growth and development. Objective: To assess nutritional status and food consumption frequency adequacy in relation to dietary guidelines in schoolchildren of high-altitude regions from northwest of Argentina. Methods: The study involved a sample of schoolchildren. Anthropometric and biochemical data were collected. The metabolic syndrome risk factors were defined following cook criterion. A nutritional questionnaire containing the main food groups was used. Economic and educational levels of household were analyzed. Results: The sample consisted of 242 children, being the mean age 8.8 ± 2.0. Undernourished (2.2%), low weight (12.7%), overweight (12.7%) and obese (7.4%) children were observed. Stunting and obesity coexist. Dietary patterns showed high intake of simple carbohydrates, sugar products and do not comply with the recommendations of the Argentinean food guidelines. Household income observation showed low economic level. An elevated proportion of children presented metabolic syndrome (18.2%). Taking into account ionic calcium calculation, 35.6% of them showed deficiency of this mineral. Conclusions: Problems of malnutrition due to excess or deficient intake of nutrients were found. The existence of inadequate dietary patterns combined with physical inactivity increases the risk of chronic disease.